2020
DOI: 10.4028/www.scientific.net/kem.838.74
|View full text |Cite
|
Sign up to set email alerts
|

Building Materials as Potential Emission Sources of VOC in the Indoor Environment of Buildings

Abstract: People spend most of their time in various indoor spaces and their health is exposed to different kinds of air pollutants. Volatile organic compounds (VOCs) belong to a group of chemical substances polluting the indoor environment. They come into the interior of buildings mainly from internal sources in the form of building materials, flooring, composite wood products, adhesives and other consumer products. Their presence in indoor air is monitored, due to their carcinogenic and mutagenic effects on human heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The general outdoor and indoor sources as well as parameters affecting the concentrations of all those contaminants are already well known (see eg, references for: CO, 19,20 NO 2 , [20][21][22][23] PM, [24][25][26][27][28] UFP, [29][30][31][32][33][34][35] VOC, [36][37][38][39][40][41] HCHO, 20 O 3 , 21,42 bioparticles 43 ). There are also many international reports by WHO 20,21,44 as well as epidemiological and other studies summarizing and showing a scientific evidence of several possible health effects of those contaminants (see eg, references for CO, 20,44 NO 2 , 20,[45][46][47][48][49] PM, 28,50,51 UFP, 52,53 DBP, 35,[54][55][56][57] VOC, [36]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general outdoor and indoor sources as well as parameters affecting the concentrations of all those contaminants are already well known (see eg, references for: CO, 19,20 NO 2 , [20][21][22][23] PM, [24][25][26][27][28] UFP, [29][30][31][32][33][34][35] VOC, [36][37][38][39][40][41] HCHO, 20 O 3 , 21,42 bioparticles 43 ). There are also many international reports by WHO 20,21,44 as well as epidemiological and other studies summarizing and showing a scientific evidence of several possible health effects of those contaminants (see eg, references for CO, 20,44 NO 2 , 20,[45][46][47][48][49] PM, 28,50,51 UFP, 52,53 DBP, 35,[54][55][56][57] VOC, [36]…”
Section: Introductionmentioning
confidence: 99%
“…The general outdoor and indoor sources as well as parameters affecting the concentrations of all those contaminants are already well known (see eg, references for: CO, 19,20 NO 2 , 20‐23 PM, 24‐28 UFP, 29‐35 VOC, 36‐41 HCHO, 20 O 3 , 21,42 bioparticles 43 ). There are also many international reports by WHO 20,21,44 as well as epidemiological and other studies summarizing and showing a scientific evidence of several possible health effects of those contaminants (see eg, references for CO, 20,44 NO 2 , 20,45‐49 PM, 28,50,51 UFP, 52,53 DBP, 35,54‐57 VOC, 36‐40,58 HCHO, 20,35,59 O 3 , 42,60,61 bioparticles 43,44,62‐64 ). However, the knowledge of the exposure to these pollutants in different sports facilities is very scattered and limited.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the CO2 produced by respiration, IAQ is reduced by emissions from the building, furniture, equipment and people (Korhonen, 2011;Rivas et al, 2019;Guo et al, 2020;Harčárová et al, 2020). Human action, upholstery materials and cigarette smoke also affect the quality of indoor conditions.…”
Section: Background and Related Standardsmentioning
confidence: 99%
“…The reaction product is one of the sources of VOCs. Katarína Harčárová et al 16 found indoor sources of VOCs mainly include building materials, flooring, composite wood products, adhesives and other consumer products. Factors that can affect types and concentrations of indoor VOCs include the number of occupants, interior decorations, relative humidity, building age and location, the extent of air pollution, ventilation intensity, season and the type of heat source, etc.…”
Section: Introductionmentioning
confidence: 99%